Paleogene paleogeographic reconstructions of the Kutai Basin: Refinement based on outcrop and subsurface data - Darman, Herman (Ikatan Ahli Geologi Indonesia, 2023)
The Kutai Basin is a Cenozoic sedimentary basin located in the eastern part of Borneo Island. Many studies were done on the eastern part of the basin, which is dominated by Neogene sediments. The west margin of the basin is outcropped onshore and to the east, the basin opens up to the Makassar Strait. Paleogene and older rocks outcrop in the west margin of Kutai Basin. The terrain and the access to the area are difficult and no significant hydrocarbon discovery was made in Paleogene sediments up to now.This study revisited the field works completed in the 1970s by a Shell team, which focused on the Paleogene section of the Kutai Basin. The result was integrated with later studies, and altogether were synthesized into a series of paleogeographic maps. A new set of paleogeographic maps is proposed in this paper, for Middle Eocene, Late Eocene, Early Oligocene, and Late Oligocene levels. The works included in this study comprised outcrop observations, biostratigraphy analysis of the samples and limited seismic in parts of the area. The results were integrated with other more recent work to build the new set of Paleogene paleogeographic maps.Outcrops data and well information show the distribution of shallow marine sediment in the Middle Eocene time with some fluvial input from the north and southwest of the basin. In the Late Eocene, some carbonates developed in the north of the basin. During Early Oligocene, the carbonate complex developed both in the south and in the north of the basin. In the Late Oligocene, the carbonate in the south became more stable. Through Paleogene time the center of Kutai Basin was dominated by the bathyal section.